The Effect of Financial Performance on Stock Return in Coal Mining Companies Registered in Indonesia Stock Exchange - Rony Marthin Sitohang; Iman Sofian Suriawinata; Rimi gusliana (Indonesian Journal of Business, Accounting and Management (IJBAM), 2019)
Abstract—This study aims to examine the effect of profitability, liquidity, asset structure, and company size on the capital structure of mining companies in this study aims to examine whether there is an influence of the current ratio, debt to equity ratio, total asset turnover and return on assets on stock returns on the company coal mining which is listed on the Indonesia Stock Exchange (IDX). This study uses a comparative research type, which is measured using a method of multiple linear regression based on the Eviews 11 program. The population of this study is coal mining companies listed on the Indonesia Stock Exchange (BEI) in 2013 to 2017. The sample is determined based on the method purpose sampling, with a total sample of 19 coal mining companies so that the total observations in this study were 95 observations. The data used in this study are secondary data. Data collection techniques use the method of documentation through the official website of IDX: www.idx.co.id, www.investing.com and www.sahamok.com. Hypothesis testing using t test. The results prove that CR, DER and ROA affect the coal mining company hospitals listed on the Indonesia Stock Exchange in the 2013-2017 period. While TATO has no effect on the coal mining company hospitals listed on the Indonesia Stock Exchange in the 2012-2017 period.